A clinical case of post-concussion syndrome in an elite professional football player - A. V. Borisova; M. R. Zhuravleva; F. V. Takhavieva; M. S. Bytovsky (National Electronic Information Consortium (NEICON), 2024)
Objective: to demonstrate our own clinical case of an athlete with an unusual post-concussion syndrome after repeated concussion of the brain.Materials and methods: presentation of own clinical observation in dynamics of a professional football player with repeated concussion of the brain complicated by post-concussion syndrome with laboratory-instrumental diagnostic methods.Results: a professional football player, as a result of a re-diagnosed concussion of the brain, had headaches, mainly in the temporal and occipital regions, weather dependence, subfebrility, while there was no effect from taking nonsteroidal anti-inflammatory drugs. As a result of instrumental examinations, changes in MCT and MRI were revealed. The conducted examinations, methods of treatment, the plan of an individual rehabilitation program are described.Conclusion: this clinical case is of great interest to practicing sports doctors, due to frequently recurring head injuries, especially in contact sports and the lack of an algorithm for treatment and rehabilitation of highly qualified athletes.